A His‐Tagged Melanocarpus albomyces Laccase and its Electrochemistry upon Immobilisation on NTA‐Modified Electrodes and in Conducting Polymer Films. Issue 10 (11th June 2013) - Sosna, Maciej; Boer, Harry; Bartlett, Philip N.
Abstract The article describes the construction, immobilisation and electrochemistry of histidine tagged laccase from Melanocarpus albomyces. A facile method of functionalisation of glassy carbon electrodes with nitrilotriacetic acid (NTA) using diazonium grafting and solid state chemistry is described. NTA‐modified electrodes are shown to bind laccase which reduces oxygen at neutral pH in the presence of soluble redox mediator. Laccase‐modified electrodes are also prepared by enzyme immobilisation within poly(aniline)/poly(vinylsulfonate) films. The polymer is found to efficiently retain the enzyme as well as provide direct electrical contact between the electrode and the enzyme active centre. Cyclic voltammetry reveals the direct electron transfer to the enzyme is dependent on the redox state of the polymer film.